Irish gombeenman - re-incarnation or rehabilitation - Gibbon, Peter; Higgins, M.D. (Economic & Social Studies, 1977)
Mr. Kennedy (1977) makes four main criticisms of our paper. These will be discussed in turn. In the process, we will be concerned not only to defend our original position, but, where possible, to correct and clarify it.
Keywords: Ireland; Sociology